Web-Based Internship Information System at SMK Nusantara 1 Kotabumi Using the Waterfall Method Approach - Trio Muhamad Sanjaya; Khusnul Khotimah (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to design and develop a web-based internship information system for SMK Nusantara 1 to support the administration of students’ industrial work practice. The existing PKL administration process still relies heavily on manual recording using paper forms and spreadsheets, which often leads to data duplication, document loss, and delays in report preparation. The proposed system was developed using the Waterfall model, which includes requirement analysis, system and database design using Unified Modeling Language (UML), implementation with PHP and MySQL, and functional testing through black-box methods. The system provides several main features, including user authentication, management of student and supervisor data, industry placement, daily activity input, supervisor assessment, final report submission, and PKL recap reporting. Testing results indicate that all functional requirements perform correctly, and users—including administrators, school supervisors, company supervisors, and students—reported that the system is easier to use compared to previous manual procedures. Overall, the system enhances transparency, reduces administrative errors, and improves the school’s ability to monitor and evaluate internship activities effectively.